Gender-Based Sustainable Disaster Response Education to Anticipate the Problem of Women’s Vulnerability - Hartono, Yudi (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
This study revealed the condition of women during a disaster in Indonesia, roles, rights and their fulfilment, and anticipates the problem of women's vulnerability in disasters. The method used was a literature study. Sources of data were from books, journals, research reports, mass media and other relevant literature sources. Data validation was done using source triangulation. The data was analyzed using interactive analysis. The results show that the condition of women during a disaster in Indonesia was faced with various vulnerabilities which resulted in a large percentage of the number of victims. However, in of such vulnerabilities, women could act as a driving force for their families and their environment to take disaster risk reduction actions. Women struggled to maintain the survival of their families and society, although, on the other hand, their rights tended to be neglected due to gender-biased socio-cultural constructions. The rights of women could not be properly guaranteed and it became even more difficult during a disaster. Women's vulnerability can be anticipated with gender-based sustainable disaster responses education that involves men and women with attention to women's rights during a disaster through formal and non-formal education.